Community-Based Hypertension Screening and Mindfulness Intervention in Awu Village, Banggai Regency - Nurarifah; Tampuyak, Irawati (Jurusan Keperawatan Politeknik Kesehatan Kementerian Kesehatan Palu, 2025)
Background: Hypertension is a major modifiable risk factor for cardiovascular disease. Community-based programs that combine screening, education, and practical self-management skills are crucial for its prevention and control. Objective: This community service initiative aimed to implement and evaluate such a program in Awu Village. Methods: The program consisted of three integrated components: (1) blood pressure screening for all participants, (2) educational sessions on non-communicable diseases and hypertension, assessed by pre- and post-tests, and (3) a practical mindfulness training session introducing techniques for stress management. Results: Screening of 45 participants revealed a high prevalence of pre-hypertension (42.2%), indicating a significant risk for progression to clinical hypertension. The educational intervention successfully improved knowledge, with the proportion of participants in the